Nanophotonic devices and circuits based on colloidal quantum dots. (20th April 2021) - Chen, Jianjun; Rong, Kexiu
Abstract : Colloidal quantum dots provide a powerful platform to achieve numerous classes of solution-processed photonic devices. This review summarizes the recent progress in CQD-based passive and active nanophotonic devices as well as nanophotonic circuits. Abstract : Colloidal quantum dots (CQDs), semiconductor nanocrystals capped with surfactant ligands and dispersed in solution, have provided a powerful platform for the achievement of numerous classes of solution-processed photonic and optoelectronic devices over recent years. They exhibit a plethora of outstanding properties, such as cost-effective synthesis, wide size-tunable emission (or absorption), large-scale solution-processable fabrication, and impressive photostability. Based on these properties achieved by novel material and structure engineering, these CQD-based photonic and optoelectronic devices are appealing alternatives to costly semiconductor products. Furthermore, a combination of these devices enables the construction of CQD-based nanophotonic circuits, which are generally composed of various components for light generation, guiding, manipulation, and detection in a single chip. In this review, we firstly summarize optical properties of CQDs, and then CQD-based passive and active nanophotonic devices, and nanophotonic circuits are also introduced and discussed. Lastly, further developments and challenges of CQD-based nanophotonic devices and circuits are outlined.